Media Pembelajaran Praja Muda Karana (Pramuka) Berbasis Android - Yusrina Ruzana Yusrina; Ari Sellyana; Tri Handayani (JUTEKINF (Jurnal Teknologi Komputer dan Informasi), 2024)
Pramuka stands for Praja Muda Karana which is a mandatory extracurricular activity that students must take part in at school, and has the aim of forming the personality, skills and noble character of young people. The scout learning process that is carried out at SMAN 5 Dumai still uses pocket books that have a simple appearance with a small size and will have the potential to experience loss, making it difficult for students to have to buy pocket books again. Researchers designed and created an android-based scout application to make it easier for students and teachers in the teaching and learning process. Researchers used the Multimedia Development Life Cycle (MDLC) method in conducting research. The development of the MDLC method was carried out based on six stages, namely concept, design, material collecting, assembly, testing and distribution. This learning media produces material in the form of animated videos and in its manufacture uses Adobe Animate with the Action Script 3.0 programming language. Evaluation of the testing of the scout learning media application was carried out by filling out a research questionnaire containing 10 questions and 20 respondents. Based on the calculation results of data processing in the questionnaire, it produces a percentage of 91.7% and is included in the very good category. This application is expected to help scout teachers and students in the process of scout learning activities.